Cal Polytechnic School (1908)
Front elevations of Household Arts, Weeks Administration Building, and Dormitory; color printed. (Addressed to Mrs. H. Victors, San Jose; postmarked Aug. 1908; M. Rieder, Publ., Los Angeles, no. 4591, Made in Germany)